1989
DOI: 10.1111/j.1752-7325.1989.tb02086.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Water Fluoridation

Ernest Newbrun

Abstract: The efficacy of communal water fluoridation in reducing dental caries has been reviewed based on surveys conducted in the last decade of caries prevalence in fluoridated and nonfluoridated communities in the United States as well as in Australia, Britain, Canada, Ireland, and New Zealand. The efficacy is greatest for the deciduous dentition, with a range of 30-60 percent less caries in fluoridated communities. In the mixed dentition (ages 8 to 12), the efficacy is more variable, about 20-40 percent less caries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
73
2
7

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(86 citation statements)
references
References 37 publications
4
73
2
7
Order By: Relevance
“…In an extensive review of studies conducted between 1979 and 1989, Newborn has found a difference of 15% to 35% in caries experience between fluoridated and non fluoride areas. The findings of this study are slightly less compared to the ones reported by Newborn [14].…”
Section: Children With Fluorosiscontrasting
confidence: 97%
“…In an extensive review of studies conducted between 1979 and 1989, Newborn has found a difference of 15% to 35% in caries experience between fluoridated and non fluoride areas. The findings of this study are slightly less compared to the ones reported by Newborn [14].…”
Section: Children With Fluorosiscontrasting
confidence: 97%
“…6 Fluoridation of drinking water has been advocated for several decades as a universal and efficient way of decreasing dental caries, particularly in children. [7][8][9][10] Most health agencies recommend a fluoride level of 1 mg/L in drinking water. At this level, total dietary intake of fluoride in most individuals would be, at most, 2 to 3 mg/day,1' substantially less than the daily dosages of fluoride received by patients with osteoporosis.…”
Section: Introductionmentioning
confidence: 99%
“…This is because it is safe, low cost and covers a large part of the population [1][2][3][4][5][6][7] . The United States Center for Disease Control and Prevention judges the measure as one of the ten most relevant public health achievements of the twentieth century.…”
mentioning
confidence: 99%